Jagad Lelembut; A Javanese Belief System That is Constructed Through the Use of Folklore and Myth on a Supernatural Worldview - Suroyo Suroyo; Derinta Entas; Novena Ade Fredyarini Soedjiwo; Bima Maulana Putra; Antonia Soriente; Fatmahwati Adnan (Javanologi: International Journal of Javanese Studies, 2025)
Javanese society deeply embraces the supernatural, with cultural belief in forming a core of their cultural identity. However, a comprehensive understanding of the roots of this belief system within Javanese culture remains limited, particularly in how myths and folklore intersect with historical and cultural contexts to shape contemporary supernatural worldviews. This study aimed to elucidate the formation, evolution, and integration of supernatural beliefs into the daily lives of Javanese people, addressing a significant research gap in Indonesian cultural studies. Employing a cross-sectional approach with qualitative analysis, data were gathered through in-depth interviews with eight knowledgeable individuals from Yogyakarta, Central Java, and East Java, and participant observation in Yogyakarta museums and cultural centers. The analysis revealed that myths and mystics folklore often serve as explanations for unexplained natural phenomena, fostering a complex cosmology where spirits and supernatural forces are integral to everyday existence. The prevalence of these narratives is significantly shaped by Java's historical and cultural trajectory. This study underscores the enduring significance of traditional beliefs in Javanese society and contributes novel insights into the intersection of folklore, history, and contemporary supernatural worldviews in Indonesia. Future research could explore the impact of contemporary influences like popular culture, social media, and globalization on these perceptions and engagements